Comparative analysis of dental-derived stem cells and alternative stem cell sources: properties and regenerative functions - Yang, Kexin; Yuan, Shengmeng; Wang, Yuhao; Lin, An; Huo, Fangjun; Jin, Zhaorui; Yang, Chao; Tian, Weidong (Frontiers in Bioengineering and Biotechnology, 2025)
Due to their accessibility, wide range of sources and unique biological characteristics, dental stem cells have broad application prospects in regenerative medicine. This cell population mainly includes dental pulp stem cells, periodontal ligament stem cells, stem cells from deciduous teeth, and dental follicle stem cells. In addition, dental stem cells have good microenvironment-specific immunomodulatory functions, including inhibiting T cell activation, promoting the polarization of regulatory T cells and regulating the phenotype of macrophages, thereby promoting tissue repair and reducing inflammation. These advantages are complemented by its strong osteogenic differentiation ability, providing a new strategy for oral tissue regeneration, and providing broad prospects for the treatment of nervous system related diseases due to its ectodermal homology with neural crest. This review systematically summarizes the major advantages of dental stem cells in the field of regenerative medicine, outlines current progress in clinical translation, and discusses future research directions, while critically comparing their therapeutic potential and challenges with other mesenchymal stem cells sources to guide seed cell selection and clinical applications.